Mapping alexithymia: level of emotional awareness differentiates emotion-specific somatosensory maps - Lloyd, Chantelle S.; Stafford, Erin; McKinnon, Margaret C.; Rabellino, Daniela; D’Andrea, Wendy; Densmore, Maria; Thome, Janine; Neufeld, Richard W. J.; Lanius, Ruth A. (Child abuse & neglect, 2021)
Background - Emotions have been associated with culturally universal and distinct bodily sensation “maps”. Despite this knowledge, to date few studies have explored emotion-specific topography along clinically relevant dimensions, such as alexithymia. - Objective - We aimed to investigate emotion-specific topographies among individuals exposed to childhood maltreatment or neglect with absent (n = 51) or with probable (n = 46) alexithymia in adulthood, as defined by scores on the Toronto Alexithymia Scale (TAS-20). - Participants and setting - Ninety eight adult participants with exposure to childhood maltreatment or neglect were recruited to complete an online survey. - Methods - Using the well-validated emBODY tool (Nummenmaa et al., 2014), participants reported on their somatic experience of 17 emotions. - Results - Random effects analyses revealed topographically distinct bodily sensation t-maps that differentiated participants who endorsed probable alexithymia from those who did not (p-FDR < .05). Consistent with our a priori hypothesis, the probable alexithymia group reported a muted, diffuse and undifferentiated pattern of emotion-specific bodily sensation, whereas the non-alexithymia group reported a more distinct and localized pattern. - Conclusions - These results suggest that difficulty identifying and labeling emotions, as observed in alexithymia, may arise, in part, from an altered perception of somatic activation. It is well-established that childhood maltreatment predicts the development of alexithymia symptoms. The preliminary findings presented here expand our working understanding of the physical markers of childhood trauma, which may be used in practice to aid detection and to monitor treatment outcomes.
Gesehen am 09.06.2021